Projection of acoustic fields using the Fourier transform - Yudelman, Errol (Department of Electrical Engineering, 2014)
A method is presented for projecting acoustic fields using the Fourier transform. It is shown that the source velocity distribution can be represented by a number of sinusoids. Each sinusoid gives rise to a plane wave whose direction is given by the wavelength of the sinusoid. The plane waves are summed at the plane of interest to obtain the resulting pressure field. Errors are introduced when projecting pressure fields by large distances. These are circumvented by observing that the farfield pressure pattern can be found by simply taking the Fourier transform of the nearfield pressure distribution. A rectangular source is simulated on the computer; the Fourier transform technique of projecting fields is compared to a direct integration technique. The Fourier transform technique is used to back project a measured pressure pattern to detect defects on the transducer face. Measurements of pressure are made in the nearfield of a circular transducer. These measurements are forward and back projected to give the pressure and velocity at other planes.